2022
DOI: 10.1007/s00405-022-07612-3
|View full text |Cite
|
Sign up to set email alerts
|

Swallowing outcome to speech therapy intervention in resistant hypertensive patients with obstructive sleep apnea

Abstract: Purpose To evaluate (i) the outcome of swallowing therapy program on the rehabilitation of oropharyngeal dysphagia in resistant hypertensive patients with obstructive sleep apnea (OSA) and (ii) the association between the clinical and anthropometric characteristics of these individuals and this outcome. Methods This was a prospective interventional study in which resistant hypertensives diagnosed with OSA by polysomnography and dysphagia by fiberoptic endoscopic evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
0
0
Order By: Relevance
“…Standardised out-of-hospital management methods, including rehabilitation, assisted patients with Parkinson’s disease, particularly mild cases [ 8 ]. One report found that eight weeks of outpatient treatment was associated with a 78.8% improvement in treatment-resistant hypertension associated with obstructive sleep apnoea and dysphagia, as revealed by endoscopic swallowing [ 9 ]. Three-week outpatient treatment of patients with neuropathy after radiotherapy to treat mesopharyngeal cancer revealed improvements in all of the Mann Assessment of Swallowing Ability (MASA) score, the Functional Oral Intake Score (FOIS), the visual analogue scale (VAS) score, hyolaryngeal excursion, lingual-palatal pressures, and certain surface electromyographic findings; the effects persisted for up to three months [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Standardised out-of-hospital management methods, including rehabilitation, assisted patients with Parkinson’s disease, particularly mild cases [ 8 ]. One report found that eight weeks of outpatient treatment was associated with a 78.8% improvement in treatment-resistant hypertension associated with obstructive sleep apnoea and dysphagia, as revealed by endoscopic swallowing [ 9 ]. Three-week outpatient treatment of patients with neuropathy after radiotherapy to treat mesopharyngeal cancer revealed improvements in all of the Mann Assessment of Swallowing Ability (MASA) score, the Functional Oral Intake Score (FOIS), the visual analogue scale (VAS) score, hyolaryngeal excursion, lingual-palatal pressures, and certain surface electromyographic findings; the effects persisted for up to three months [ 10 ].…”
Section: Discussionmentioning
confidence: 99%